2023
DOI: 10.1097/gox.0000000000004787
|View full text |Cite
|
Sign up to set email alerts
|

Content and Readability of Online Recommendations for Breast Implant Size Selection

Abstract: Background: Breast augmentation is one of the most frequently performed aesthetic procedures in the United States. Online information is often used by patients to make decisions when undergoing cosmetic procedures. It is vital that online medical information includes relevant decision-making factors and uses language that is understandable to broad patient audiences. Ideally, online resources should aid patient decisions in aesthetic surgical planning, especially implant size selection for breast augmentation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Despite these recommendations, prior studies have elucidated the readability of patient education materials, with many studies describing that the average reading levels of education materials do not meet the national recommended average by several grade levels. 6,7,9–20 In prior studies, it is clear that many patient education materials are written above the recommended levels; however, to our knowledge, this is the first study to offer a simplified solution using AI to manage and improve patient health education materials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these recommendations, prior studies have elucidated the readability of patient education materials, with many studies describing that the average reading levels of education materials do not meet the national recommended average by several grade levels. 6,7,9–20 In prior studies, it is clear that many patient education materials are written above the recommended levels; however, to our knowledge, this is the first study to offer a simplified solution using AI to manage and improve patient health education materials.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, patient-facing materials in plastic surgery often remain at an above-recommended average reading level. 9–20…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,16,19,20,22 However, recent studies have shown that online plastic surgery resources often exceed the recommended sixth grade reading level as suggested by American Medical Association guidelines. [23][24][25] In addition, it is unclear whether certain terminology utilized online in plastic surgery resources accurately convey the differences in training and accreditation attained by respective providers. Although there are multiple pathways to becoming a safe and effective surgeon, it is concerning that multiple studies have shown that many providers offer plastic surgery procedures in an increasingly competitive online market and often perform procedures outside of the scope of their training.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, one study identified that in plastic surgery, 50.2% of patients had an education level lower than high school and that 48% of attendings, residents, and PAs said it was challenging to make patients follow postoperative instructions [ 34 ]. Moreover, patient materials in plastic surgery are often above the recommended average reading level of 6th to 8th grade and may be too difficult for the average patient [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%